Aryl‐Copper(III)‐Acetylides as Key Intermediates in C sp 2Csp Model Couplings under Mild Conditions. Issue 32 (10th July 2014) - Rovira, Mireia; Font, Marc; Acuña‐Parés, Ferran; Parella, Teodor; Luis, Josep M.; Lloret‐Fillol, Julio; Ribas, Xavi
Abstract The mechanism of copper‐mediated Sonogashira couplings (so‐called Stephens–Castro and Miura couplings) is not well understood and lacks clear comprehension. In this work, the reactivity of a well‐defined aryl‐CuIII species (1<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghwhbv7kg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> ClO 4</alternatives>) with p‐R‐phenylacetylenes (R=NO2, CF3, H) is reported and it is found that facile reductive elimination from a putative aryl‐CuIII‐acetylide species occurs at room temperature to afford the CarylCsp coupling species (IR), which in turn undergo an intramolecular reorganisation to afford final heterocyclic products containing 2H‐isoindole (P<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghwhbvjqw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 2</alternatives>, P<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghwhbvjmb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> CF 3</alternatives>, PHa) or 1, 2‐dihydroisoquinoline (PHb) substructures. Density Functional Theory (DFT) studies support the postulated reductive elimination pathway that leads to the formation of C<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghwhbvjj9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> sp 2</alternatives>Csp bonds and provide the clue to understand the divergent intramolecular reorganisation when p‐H‐phenylacetylene is used. Mechanistic insights and the very mild experimental conditions to effect CarylCsp coupling in these model systems provide important insights for developing milder copper‐catalysed CarylCsp coupling reactions with standard substrates in the future.